Rigidity Test Using the Pebble Game Centralized Implementation - DJAIDJA, Ridha; Research Director: Moussaoui, A. (University of M'sila, 2016)
In this dissertation, we start our study With rigidity theory that can test rigidity and flexibility of bar and joint frameworks in 2 dimension. different applications related to rigidity theory have been made in several fields. This theory has facilitated the development of the pebble game algorithms, and we implement a computer program to test the rigidity and flexibility of a given graph.
Keywords: rigidity theory, rigidity, bar and joint frameworks, 2 dimension, pebble game algorithms, graphe